Isolation and expansion of allogeneic myeloma-specific interferon-gamma producing T cells for adoptive immunotherapy - Ocadlikova, Darina; Zahradova, L; Kovarova, L; Penka, M; Zaloudik, J; Buchler, T; Hajek, R; Michalek, J (Medical oncology (Northwood, London, England), 2006)
Adoptive immunotherapy is a promising approach in the treatment of multiple myeloma. We have tested the identification, separation, and expansion of allogeneic myeloma-specific T cells in vitro. Irradiated myeloma cell line ARH 77 has been used to stimulate allogeneic CD4(+) and CD8(+) T lymphocytes. Activated myeloma-specific T cells that produced interferon-gamma were isolated using immunomagnetic beads and further expanded in vitro to numbers of up to 400 x 106 T cells. Specificity of the T lymphocytes was tested using a 5-(6-)carboxyfluoresceine diacetate succinimidyl ester (CFSE)-based cytotoxicity test. This study demonstrates the feasibility of identification and isolation of tumor-specific T cells from allogeneic donors that can be expanded in vitro to numbers useful for clinical applications.
Keywords: Fluoresceins; Humans; Magnetics; T-Lymphocytes; Succinimides; Multiple Myeloma; magnetismus; separace buněk; lidé; CD8-Positive T-Lymphocytes; časové faktory; Transplantation, Homologous; CD8-pozitivní T-lymfocyty; mnohočetný myelom; Immunotherapy, Adoptive; CD4-Positive T-Lymphocytes; fluoresceiny; sukcinimidy; lékařská onkologie; Cell Separation; CD4-pozitivní T-lymfocyty; interferon gama; T-lymfocyty; Cell Culture Techniques; imunoterapie adoptivní; homologní transplantace; Time Factors; Interferon-gamma; buněčné kultury; Medical Oncology